Treatment stigma mediates relationships between morally injurious events and depression, PTSD and anxiety symptoms - Shilat Haim-Nachum; Amit Lazarov; John C. Markowitz; Maja Bergman; Yossi Levi-Belz; Ido Lurie; Milton L. Wainberg; Shlomo Mendlovich; Yuval Neria; Doron Amsalem (European Journal of Psychotraumatology)
Background: Morally injurious events (MIEs), encompassing personal transgressions, witnessing others commit transgressions, or experiencing betrayal by leaders, can conflict with one's moral/ethical principles, evoking outrage and profound mistrust. Although MIEs are associated with depression, PTSD, and anxiety, the mechanisms linking MIEs to psychiatric symptomatology remain unclear, especially among civilians in times of collective trauma.Objective: This study explored one potential mechanism: stigma toward mental-health treatment, which can deter help-seeking and exacerbate guilt, shame, and mistrust.Method: We focused on civilians (N = 1,052) exposed to MIEs in conflict zones in southern and northern Israel following the 7 October 2023 attack. Participants were recruited using an online platform and assessed for depression, PTSD, and anxiety symptoms. We hypothesised that stigma toward treatment would mediate relationships between MIE exposure levels and depression, PTSD, and anxiety symptoms.Results: Results showed high MIE exposure levels and symptomatology among civilians in conflict zones. Moreover, we found significant indirect effects of stigma toward treatment on all three symptom types.Conclusions: Our findings suggest that while MIEs directly link to symptoms, stigma toward treatment plays a significant role in understanding this link. These findings emphasise the importance of addressing stigma toward treatment for individuals experiencing MIEs and underscore the need for targeted interventions in conflict zones.